Pembentukan Peraturan Pemerintah Pengganti Undang-Undang Pasca Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 - Bachmid, Fahri (Universitas Tribhuwana Tunggadewi, 2023)
Constitutional Court, through Decision No. 91/PUU-XVIII/2020, states that the Job Creation Law is conditionally unconstitutional, so the Government is asked to amend the Job Creation Law within the last two years. The Government did not implement the Job Creation Law as mandated by the Constitutional Court Decision. Instead, the Government stipulated the Job Creation Perppu as a substitute for the Job Creation Law, which had been declared formally flawed by the Constitutional Court. Problems arising from the stipulation of the Job Creation Perppu include the stipulation of the Work Creation Perppu; and the implication of the enactment of Perppu by the Government after the Constitutional Court Decision No. 91/PUU-XVIII/2020. This study aims to find out the various polemics and implications of the enactment of Perppu by the Government after the Constitutional Court Decision No. 91/PUU-XVIII/2020. The research method used is normative legal research in the form of library research. The data collection technique used in this study was a literature study which was then analyzed qualitatively. The research results obtained are that the Job Creation Perppu is not in line with the Constitutional Court decision No. 91/PUU-XVIII/2020, reasons for urgency that force cannot be assumptive and calculative, basic principles and juridical parameters in constructing a nature and precarious situation that compels constitutional limits have been formulated by the Constitutional Court in Decision Number 138/PUU-VII/2009.AbstrakMahkamah Konstitusi melalui Putusan No. 91/PUU-XVIII/2020 menyatakan bahwa UU Cipta Kerja inkonstitusional bersyarat, sehingga pemerintah diminta untuk memperbaiki UU Cipta Kerja dalam dua tahun ini. Atas hal tersebut pemerintah tidak melaksanakan sebagaimana amanat Putusan Mahkamah Konstitusi, namun menetapkan Perppu Cipta Kerja sebagai pengganti UU Cipta Kerja yang telah dinyatakan cacat formil oleh Mahkamah Konstitusi. Permasalahan yang timbul dari penetapan Perppu Cipta Kerja, antara lain: penetapan Perppu Cipta Kerja; dan implikasi ditetapkanya Perppu oleh pemerintah pasca Putusan Mahkamah Konstitusi No. 91/PUU-XVIII/2020. Tujuan dari penelitian ini yaitu untuk mengetahui berbagai polemik dan implikasi ditetapkanya Perppu oleh pemerintah pasca Putusan Mahkamah Konstitusi No. 91/PUU-XVIII/2020. Metode penelitian yang digunakan yaitu penelitian hukum normatif berupa penelitian kepustakaan (library research). Teknik pengumpulan data yang dilakukan dalam penelitian ini adalah studi kepustakaan yang kemudian dianalisis secara kualitatif. Hasil Penelitian yang diperoleh yaitu Perppu Cipta Kerja tidak sejalan dengan putusan Mahkamah konstitusi No. 91/PUU-XVIII/2020, alasan kegentingan yang memaksa tidak boleh asumtif serta kalkulatif, prinsip dasar dan parameter yuridis dalam mengkonstruksikan suatu sifat dan keadaan kegentingan yang memaksa telah dirumuskan batasan konstitusionalnya oleh Mahkamah Konstitusi dalam Putusan Nomor 138/PUU-VII/2009.